Implementation Support of Security Design Patterns Using Test Templates - Yoshizawa, Masatoshi; Washizaki, Hironori; Fukazawa, Yoshiaki; Okubo, Takao; Kaiya, Haruhiko; Yoshioka, Nobukazu (Information (Basel), 2016)
Security patterns are intended to support software developers as the patterns encapsulate security expert knowledge. However, these patterns may be inappropriately applied because most developers are not security experts, leading to threats and vulnerabilities. Here we propose a support method for security design patterns in the implementation phase of software development. Our method creates a test template from a security design pattern, consisting of an “aspect test template” to observe the internal processing and a “test case template”. Providing design information creates a test from the test template with a tool. Because our test template is reusable, it can easily perform a test to validate a security design pattern. In an experiment involving four students majoring in information sciences, we confirm that our method can realize an effective test, verify pattern applications, and support pattern implementation.